Acute effects of the RAMP warm-up on sprint and jump performance in youth soccer players - Girginer, Fatma Gözlükaya; Seyhan, Sinan; Açar, Görkem; Bilici, Muhammed Fatih; Bilici, Ömer Faruk; Soylu, Çağlar (Frontiers in Physiology, 2025)
IntroductionPre-competition warm-ups play a critical role in optimizing athletic performance and minimizing injury risk. This randomized, controlled crossover study investigated the acute effects of the Raise, Activate, Mobilize, and Potentiate (RAMP) warm-up protocol on key performance parameters in young male soccer players.MethodsFourteen participants (aged 16–22 years) completed three different warm-up conditions—no warm-up (control), static stretching, and RAMP—on non-consecutive days with a 48-h washout period. Performance was assessed using 30-m sprint and vertical jump tests, each performed twice per session with the best trial recorded for analysis.ResultsA one-way repeated-measures analysis of variance (ANOVA) revealed that both vertical jump height and sprint performance differed significantly across conditions (p < 0.05). Post hoc Bonferroni comparisons indicated that the RAMP group exhibited superior results compared with static stretching (Effect size: d = 0.41) and control (Effect size: d = 0.52), while no notable difference was observed between static stretching and control conditions.DiscussionThese results suggest that the structured progression of the RAMP protocol—combining exercises that elevate body temperature, activate key muscle groups, improve mobility, and enhance neuromuscular readiness—can acutely enhance explosive strength and sprint speed by effectively priming the neuromuscular system. This study contributes novel insights by demonstrating the acute efficacy of the RAMP method in youth soccer players, a population that has been underrepresented in previous literature. Although the study was limited to male amateur athletes and focused on short-term performance gains, the findings indicate suggestive potential for implementing the RAMP protocol as an evidence-based approach in pre-competition preparation.